Association Between Improved Mobility and Distal Health Outcomes. (9th April 2020) - Shuman, Valerie; Coyle, Peter C; Perera, Subashan; Van Swearingen, Jessie M; Albert, Steve M; Brach, Jennifer S
Abstract: Background: We examined the association between improved mobility and distal health outcomes in older adults using secondary analysis of data from a cluster-randomized controlled group exercise trial. Methods: Participants were 303 men and women aged ≥65 and older in 32 independent living facilities, senior apartments, and community centers who participated in 12-week group exercise interventions. Included were those who completed ≥1 follow-up phone call regarding outcomes assessment in the following year. Gait speed and 6-minute walk distance (6MWD) were assessed at baseline and immediately after 12-week interventions to determine mobility performance change status. Falls, emergency department (ED) visits, and hospitalizations were assessed monthly for 12 months following the end of interventions via interactive voice response phone calls. Incident rate ratios (IRRs) were calculated to quantify incidence of adverse outcomes with respect to mobility performance change. Results: Each 0.05 m/s increase in gait speed resulted in an 11% reduction in falls (IRR = 0.89; 95% confidence interval [CI], 0.84–0.94; p < .0001); a similar decrease was seen for each 20 m increase in 6MWD (IRR = 0.89; 95% CI, 0.83–0.93; p = .0003). Those who improved gait speed had 61 falls per 1, 000 person-months versus 135 in those who had no change/a decline. Those who improved 6MWD had 67 falls per 1, 000 person-months versus 110 per 1, 000 person-months in those who had no change/a decline. Differences in ED visits and hospitalizations were not statistically significant. Conclusion: Improvements in mobility performance are associated with lower incidence of future falls. Given the exploratory nature of the findings, further investigation is warranted.